Ataxic Severity Is Positively Correlated With Fatigue in Spinocerebellar Ataxia Type 3 Patients - Yang, Jin-Shan; Xu, Hao-Ling; Chen, Ping-Ping; Sikandar, Arif; Qian, Mei-Zhen; Lin, Hui-Xia; Lin, Min-Ting; Chen, Wan-Jin; Wang, Ning; Wu, Hua; Gan, Shi-Rui (Frontiers in Neurology, 2020)
Background Spinocerebellar ataxia type 3 (SCA3) is an inherited form of ataxia that leads to progressive neurodegeneration. Fatigue is a common non-motor symptom in SCA3 and other neurodegenerative diseases, such as Parkinson's disease (PD) and amyotrophic lateral sclerosis (ALS). Although risk factors to fatigue in these diseases have been thoroughly studied, whether or not fatigue can affect clinical phenotypes has yet to be investigated.91 molecularly confirmed SCA3 patients and 85 age and sex-matched controls were recruited for this study. The level of fatigue was measured using the 14-item Fatigue Scale , and the risk factors to fatigue and how fatigue affects clinical phenotypes were studied using multivariable linear regression models.We found that the severity was significantly higher in the SCA3 group than in the control group (9.30 ± 3.04 % vs. 3.94 ± 2.66, P = 0.000). Daytime somnolence (β = 0.127, P = 0.024), severity of ataxia (β = 0.053, P = 0.040) and the length of expanded CAG repeats (β = 0.224, P = 0.046) were found to have a positive influence on fatigue. Although fatigue had no influence on age at onset or ataxic progression, we found that it did have a positive effect on the severity of ataxia (β = 0.965, P = 0.040).The high level of fatigue and the impact of fatigue on the clinical manifestation of SCA3 patients, suggests that, fatigue plays a large role in the pathogenesis of SCA3, thus demonstrating the need for intervention and treatment options in this patient cohort.